Integral approach to control information postprocessing in the system for the automatic programming of flexible manufacturing systems for the machining of rotational parts - Hodolič, Janko (Journal of Production Engineering, 1990)
The paper starts with definition of the postprocessor in narrow and extended sence. It is pointed out that introduction of standardization within CNC units programming languages did yet decrease necessity for postprocessing. It’s also emphasized that a number of developed generalized postprocessors and their generators originate from researches performed due to postprocessors development. In the paper the original model of postprocessing system is presented. The postprocessor which is shown belongs to the group of post-processors in extended since based on integral approach to postprocessing for CNC machine tools for rotational parts machining, for measuring machines and manipulation systems. The system is considered to be a part of the complex technologically oriented system for automatic programming of flexible technological systems, having simple regeneration abilities. The presentation of the model is performed through four subsystems: input information’s subsystem, in-formation basis subsystem, the main program with accompanied segments and output information’s subsystem. The model of the main computer program is organized as matrix structure with rows representing postprocessing phases and columns representing postprocessing branches. The branches are dedicated to postprocessing of control information’s for particular FTS com-ponents such as CNC machine tools, industrial manipulators, measuring machines, transport systems etc. The most important question, among a number existing, due to development of the proposed and partially tested postprocessing system, seems to be development of metalanguage intended to describe programming languages for CNC units belonging to flexible technological systems.